(untitled) (Singaporean Journal of Business Economics and Management, 2018)
The current article was design to determine the relationship between students’ satisfaction and CRM (customer relationship management) in different universities. The main objective of the study was to find out the awareness about CRM in Pakistani universities and its impact on students’ life. Both descriptive and inferential statistics were applied in research work. This research was based on the customer relationship management practices and customer satisfaction in the higher education institute of Lahore, Pakistan. The sample was selected only from private HEI according to their populations. The results were conducted through statistical software SPSS. This study has cleared not only the relationship between CRM and customer satisfaction, but also has explained the moderating effect of students in this relationship. On the basis of results, it can be predicted by the researcher that the CRM’s future will be brighter in HEI and the decision makers will take effective and impressive decisions for future work and may be decrease the gaps with international institutions. The sample sized 298 used in this research work and Questionnaires were distributed in the top three universities of Lahore Pakistan. The reliability test, correlation and linear regression tests were applied and the entire tests showed the goodness of study. Correlation and regression test showed the positive relationship of the research hypothesis. Results proved that effective used of CRM create positive impact on student’s satisfaction.